Sustainability Scenario of Islamic Leader School and Hidayatul Mustafid Agribusiness in Tasikmalaya City - Lazuardi Labunove Ismi, M. Jorgy; Nuryati, Rina; Hikmah Widi, Riantin; Setiawan, Perdi (Universitas Djuanda, 2025)
Islamic boarding school agribusiness management is currently trending. Among them, Islamic boarding schools such as the Islamic Leader School and Hidayatul Mustafid, both of which have stagnated due to the lack of a development model. The purpose of this study is to formulate a scenario for the sustainability of Islamic boarding school agribusiness in Tasikmalaya City. This scenario is needed as capital for the long-term development of Islamic boarding school agribusiness. Islamic Leader School and Hidayatul Mustafid Islamic boarding schools were purposively selected as research locations because they have consistently run Islamic boarding school-based agribusiness for more than ten years in Tasikmalaya City. To date, both Islamic boarding schools have only relied on trial and error, this is because there is no basis for designing a development model. Therefore, this research is very necessary to determine the prospects of Islamic boarding school agribusiness. The study was conducted from January to February 2025. The research method used was a case study, with data used from in-depth interviews with two key informants, two primary informants, and two supporting informants. In addition, to deepen the discussion, a literature review is needed. Furthermore, the analytical tool used was Prospective Participatory Analysis to analyze key factors in scenario development. Based on the research results, five key factors were identified as having a strong influence on the sustainability of Islamic boarding school agribusinesses: Islamic boarding school farming, learning facilities, market partnerships, farming development prospects, and farming sustainability. Furthermore, the tabulation of key factors indicated that the best scenario was moderate-optimistic